A different approach to the determination of aerobic capacity: Relative endurance method - Marangoz, I. (International Journal of Applied Exercise Physiology, 2020)
The present study aims to offer a more different approach than age-based VO2max norm tables in order to reach more detailed information regarding the development of aerobic capacity in athletes. Theresearch was carried out on 160 volunteer sub-elite male athletes from different sports branches in Kirsehir province of Turkey within an age group of 21.50±2.30 and with a weight of 74.59±7.94 kg and height of 179.41±5.45. All calculations in the presentstudy were performed using "Some Tests and Calculation Programs for the Measurement of Physical Performance" by Marangoz (2019). Finally, statistical data analysis was performed using SPSS 22.0 package program for Windows. The findings of the present study demonstrated that relative endurance was a practical and effective method for the evaluation of performance and development of aerobic capacity.